ПОСТКОВІДНІ ГЕПАТОЛОГІЧНІ УСКЛАДНЕННЯ У ХВОРИХ НА ЦУКРОВИЙ ДІАБЕТ 2 ТИПУ - Пінський, Л. Л.; Моргун, Д. Г.; Хайтович, М. В. (Українські медичні вісті, 2023)
ПОСТКОВІДНІ ГЕПАТОЛОГІЧНІ УСКЛАДНЕННЯ У ХВОРИХ НА ЦУКРОВИЙ ДІАБЕТ 2 ТИПУ